The development of a science, technology and society phenomenon-based learning model for promoting grade 12 students’ problem-solving in geohazard - Pookduang, Prom; Buaraphan, Khajornsak (Asian Journal of Education and Training, 2024)
This research aimed to: a) synthesize the Science, Technology, and Society Phenomenon-based Learning Model (STS-PhBL) for teaching Geoharzard to students; and b) compare students’ problem-solving skills prior to and after the STS-PhBL lessons on the Geoharzard topic. The sample consisted of 39 Grade 12 students enrolled in the first semester of the 2021 academic year at one secondary school in Surin Province, Thailand. The data collection methods included the panel of experts’ evaluation of STS-PhBL lesson plans and the Problem-Solving Skills Test. The Index of Item-Objective-Congruence (IOC) of STS-PhBL lesson plans on Geoharzard was calculated. Also, the students’ problem-solving skills prior to and after the STS-PhBL lessons in the Geoharzard topic were analyzed by using the paired-samples t-test. The researchers synthesized a new STS-PhBL model from the intensive literature review, consisting of seven teaching steps: a) stimulate the phenomenon; b) identify problems in the phenomenon; c) explore the answer to the targeted problem; d) construct new knowledge; e) reflect on learning; f) exchange and share learning; and g) apply knowledge. The STS-PhBL lesson plans on Geoharzard met the IOC requirements. After learning STS-PhBL lessons, the students significantly improved their problem-solving skills at the 0.05 statistically significant level.